Pelaksanaan Lelang Terhadap Jaminan Hak Tanggungan Pada Perbankan (Studi Di Kantor Pelayanan Kekayaan Negara Dan Lelang (KPKNL) Kisaran) - Mawarni Sinaga; Irda Pratiwi (Iuris Studia: Jurnal Kajian Hukum, 2020)
Marketing (auction) is meant in the discussion of this thesis is auction of mortgage rights to land, in practice it is called auction of mortgage rights over land. Based on the fact, the objects being auctioned are land rights and apartment units as stated in the mortgage rights law and government regulations. That the objective of the auction of land rights and apartment units is carried out so that consumers can use and control the land legally according to the applicable law shall be the right of the auction winner. The mortgage auction is the sale of movable and immovable property publicly with a written or direct bid price, whether it increases or decreases in the attainment of the highest price before the auction announcement, so that the committee can close and determine the auction winner with the highest bid system from the guarantor rights auction participants. Based on the provisions of the auction implementation instructions contained in PERMENKEU number 27 / PMK.06 / 2016, the meaning of Auction is the offering of movable and immovable objects open to the public and the bidding system from the lowest to the highest bid from the auction participants, the auction bid will be closed after the auction winner the one with the highest bid value